ISKANDARIA (ISKANDARIA PROKOFIEV, 2009) DISTRIBUTION OF GENUS SPECIES FRESHWATER BASINS OF THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
Nodays it has established that two species belonging to the genus Iskandaria live in the reservoirs of theFergana Valley, and they are local species. This article talks about the distribution of the Alexandrian species in thereservoirs of the valley.